The Influence of the Leadership Style of the Head of Panca Health Center on Employee Performance in 2023 - Dea kusumawati Dewi; Ahmad Zaelani; Matheus Aba (PROMOTOR, 2024)
The development of an agency is the task of a leader to make it happen. personal power and follower involvement in the problem-solving and decision-making process. Decision making and problem solving are not centered on the leader. Leaders must be able to influence their employees to be responsible in completing their work. The aim of this research is to identify the influence of leadership style on employee performance at the Panca Health Center. The design of this research is cross sectional. The population of this study was 39 Panca Health Center employees, the sampling technique was total sampling. The sample in this research was 39 Panca Health Center employees. The results of the crosstabs test using SPSS 25.0 showed that the application of leadership style at the Panca Community Health Center was more dominant using a democratic leadership style. From these results it can be seen that respondents with performance in the moderate category stated a leadership style in the high category more than the leadership style in the high category, namely 16 (41 %) respondents. And the results of the correlation coefficient test are 0.815, then for significant results the t test and f test are carried out, namely 0.000 < 0.005, which means this shows that H0 is rejected and H1 is accepted. Shows that democratic leadership style has a significant effect on employee performance. So it can be concluded that the better the leadership implemented by the head of the community health center, the more the quality and quantity of employee performance at the Panca Community Health Center will increase. In advancing an agency, cooperation between leaders and employees is needed. Leaders must be able to understand the character of employees and the conditions they face in order to create an effective leadership style. Implementing an effective leadership style can improve the quality and quantity of employee performance